Isolation, Identification, and Antibiotic Susceptibility Test of Streptococcus spp. from a Cat Suspected of Respiratory Tract Disease at Nong Lam University, Vietnam - Amalda, Elfahra Casanza; Amalia, Mifta Rizqina; Rifai, Ainrisq Auliya; Karo, Yohana Maria; Chintari, Lady Konfidenia; Palyoga, Habyb (Veterinary Biomedical and Clinical Journal, 2024)
The nasal sample of a suspected respiratory tract disease cat, which is characterized by having a yellowish-colored nasal discharge, was obtained from a clinic in Ho Chi Minh City to be brought to the laboratory using the Stuart Amies transport medium. Samples were isolated on blood agar plate (BAP) media anaerobically. Gram staining and catalase tests were performed to identify the bacterial species. Furthermore, we conducted antibiotic sensitivity tests using Mueller-Hinton Agar (MHA) media, which included Tetracycline, Gentamicin, Marbofloxacin, and Amoxicilin-Clavulanate antibiotic disks. In order to prescribe an antibiotic, a clinical vet must go through a series of decision-making processes that involve both the drug and the host. In this case study, we were performing the diagnostic process before a medication could be prescribed to a patient with suspected respiratory tract disease.